Beschreibung einer neuen Gattung der Familie Scirtidae aus der Orientalischen Region (Coleoptera)(144. Beitrag zur Kenntnis der Scirtidae). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2009)
The species of the genus Cyphon Paykull, 1799, hitherto treated as Cyphon chlorizans group, are combined in the genus Ypsiloncyphon gen. n. The new genus is characterized by derived structures of the tegmen, the 9th sternite and 8th and 9th tergite of the male as well as the 8th sternite of the female. A determination key of all known species and a catalogue with the new combinations are provided.KeywordsColeoptera, Scirtidae, Ypsiloncyphon, Cyphon, new genus, Orientalis, Paläarktis.Nomenclatural ActsYpsiloncyphon Klausnitzer, 2009 (Scirtidae), gen. n.amami (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon amamichlorizans (Klausnitzer, 1973) (Ypsiloncyphon), comb. n. hitherto Cyphon chlorizansformosus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon formosushofferi (Klausnitzer, 1973) (Ypsiloncyphon), comb. n. hitherto Cyphon hofferihonshuanus (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon honshuanusjaloszynskii (Ruta, 2004) (Ypsiloncyphon), comb. n. hitherto Cyphon jaloszynskiijiangxiensis (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon jiangxiensiskarnatakaensis (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon karnatakaensiskejvali (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon kejvaliluteoapicalis (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon luteoapicalismaharashtraensis (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon maharashtraensismahensis (Champion, 1924) (Ypsiloncyphon), comb. n. hitherto Cyphon mahensismendosus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon mendosusmicans (Klausnitzer, 1973) (Ypsiloncyphon), comb. n. hitherto Cyphon micansminutulus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon minutulusnigroflavus (Ruta, 2004) (Ypsiloncyphon), comb. n. hitherto Cyphon nigroflavusokinawanus (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon okinawanusparamicans (Klausnitzer, 1979) (Ypsiloncyphon), comb. n. hitherto Cyphon paramicanspseudoatratus (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon pseudoatratusreconditus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon reconditussinuosus (Sasagawa, 1985) (Ypsiloncyphon), comb. n. hitherto Cyphon sinuosusspinifer (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon spinifertamilensis (Ruta, 2007) (Ypsiloncyphon), comb. n. hitherto Cyphon tamilensisvoluptificus (Klausnitzer, 1980) (Ypsiloncyphon), comb. n. hitherto Cyphon voluptificusyayeyamanus (Yoshitomi, 2005) (Ypsiloncyphon), comb. n. hitherto Cyphon yayeyamanus